MENINGKATKAN MOTORIK HALUS DALAM MEMEGANG ALAT TULIS MELALUI TEKNIK MENCONGKEL BAGI ANAK AUTIS - Taurus Fitri Mila (Jurnal Penelitian Pendidikan Khusus, 2012)
The reseatch is starting from obsevation, where researcher found when realize observation. Researcher found an autis child get obstacle in take hold of pencil. This research have as aim to increase child ability in hold pencil with good and right by means of pry up flestisin technique.  This research use experiment approach in from Single Subject Research (SSR), with use A-B desian. Subject is this research is an autis child. The yield of the research shawed, if talent, if talent of autis child hold a pencil is rise although stages. In this baseline condition (A) the child can do one talent that is write distance between book and eye 25-30cm. at baseline condition in the frist day till 5th days, talented of child across that is 30%. At intervensi condition (B) straight rise from 35% till 65%. Suggestion for teacher can use pry up technique to increase how to hold pencil for autis child.